Are two bodies in a trench a mass grave? an attempt to bridge the gap between single and mass graves - Wessling, Roland; Spoletini, Allie (Equinox Publishing, 2024)
The definitions for mass graves proposed in the past concentrated on the minimum number of casualties and whether they were in a connected body matrix. This meant that many graves practitioners encounter could not be classified properly. They were neither a single grave nor a mass grave. This article proposes four key measures to address the grave classification issue. Firstly, it introduces three simple criteria to assist in classification. Secondly, it suggests three new grave types (cluster, trench, and serial grave) to name the most common graves. Thirdly, a final grave type, the multiple grave, is added to describe any grave that does not fit into any of the other categories. Finally, this article suggests that the threshold between multiple and many casualties, i.e. how many casualties constitutes a mass grave, should be set for each individual conflict or context rather than aiming for a universal figure. These four measures are designed to be simple, intuitive and flexible enough to allow practitioners to use grave labels that make sense in their particular context for forensic and legal professionals as well as the general public.
Warning: This article contains images of mass Graves from genocides, which some may find disturbing.
Keywords: grave classification; forensic archaeology; single grave; mass grave; multiple grave